Chemical Composition of the Essential Oils from Stem, Root, Fruit and Leaf of Piper longum Linn. Issue 1 (2nd January 2016) - Varughese, Titto; Unnikrishnan, Prakash Kumar; Deepak, M.; Balachandran, Indira; Rema Shree, A.B.
Abstract: The essential oil obtained from the fresh parts of root, stem, fruit, and leaf of Piper longum growing wild in Western Ghats, Kerala was analyzed by GC-MS. The study led to the identification and quantification of 38 (root), 36 (stem), 29 (fruit) and 37 (leaf) chemical constituents belonging to different classes of compounds accounting for 96.9 %, 97.2 %, 97.1 % and 76.7 % of the total oil composition respectively. The essential oil production, yield of total volatile oil content in fruit and leaf was higher than that of root and stem. The principal components in root, stem, and fruit were comparable. The oil composition of root (62.0 %), fruit (71.5 %), and stem (69.2 %) was dominated by the presence of monoterpene hydrocarbons while the leaf had sesquiterpene hydrocarbons (68.7 %) as the major components. The high amount of monoterpene, especially pinene and camphene in the root, stem and fruit due to the freshness of the sample.